PEMETAAN POTENSI EKONOMI DAERAH SECARA SEKTORAL DAN KEWILAYAHAN DI JAWA BARAT: PENDEKATAN ANALISIS INPUT OUTPUT - , Asim Saputra ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is expected to be known: (1) description of the performance indicators and the basic characteristics of economic development per block area, (2) the interaction between sectors of each economy in the block area, and identification of key sectors, (3) differences in the structure of the economy (economic landscape) inter-block area, and (4) multiplier economic sectors in terms of increased output, household income, and employment per block area in West Java. Input-Output table is a breakdown of the statistics in the form of a matrix that describes the use of goods and services transactions between various economic activities as a whole (BPS, 1995). The combination coefficient analysis Input- Output Table derivatives are used to map the potential economy by sectoral and region to be more distantly related to the economic activity. By using the data series Gross Regional Domestic Product (GRDP) of West Java, 2001-2010 and structure Table I-O per block area, produced the following research. (1) empirically, the results of the economic development of West Java performance seen yet fully able to improve the standard of living, income generation and employment opportunities in an optimal (2), most of the manufacturing industry sectors have total backward linkage and total forward linkage is high, so the key sectors of the economy is dominated these sectors in each block of West Java, (3) analysis of economic landscape discovered a strong influence on the performance of the energy supply of the sectors in the economy in the West Block and Central Block, and (4) multiplier analysis suggests at least one of the key sectors of the economy in each block area has a total effect on household income and employment are quite high, such as the building sector (West Block), the industrial sector of metal goods and industrial machinery and equipment (Central Block) and industrial sectors of metals and metal goods (Eastern Block). The analysis of MFEP confirms five priority sectors of the economy remain dominated by the manufacturing industry sectors in all the blocks of the region, which is supported by the building sector /construction (strong influence encourages the growth of economic output) and transport (strong influence as input others sectors in the economy).